Framing From Experience: Cognitive Processes and Predictions of Risky Choice. (27th August 2015) - Gonzalez, Cleotilde; Mehlhorn, Katja
Abstract: A framing bias shows risk aversion in problems framed as "gains" and risk seeking in problems framed as "losses, " even when these are objectively equivalent and probabilities and outcomes values are explicitly provided. We test this framing bias in situations where decision makers rely on their own experience, sampling the problem's options (safe and risky) and seeing the outcomes before making a choice. In Experiment 1, we replicate the framing bias in description‐based decisions and find risk indifference in gains and losses in experience‐based decisions. Predictions of an Instance‐Based Learning model suggest that objective probabilities as well as the number of samples taken are factors that contribute to the lack of framing effect. We test these two factors in Experiment 2 and find no framing effect when a few samples are taken but when large samples are taken, the framing effect appears regardless of the objective probability values. Implications of behavioral results and cognitive modeling are discussed.